The Role of Digital Transformation in Optimizing Global Supply Chain and Logistics Management Systems - Rachmat, Diar Fachmi (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Digital transformation has become a strategic factor in optimizing global supply chain and logistics management systems amidst the growing complexity of markets, uncertainty, and rapid technological advancements. This study aims to analyze the role of digital transformation through the utilization of technologies such as big data analytics, artificial intelligence, the Internet of Things (IoT), blockchain, and cloud computing platforms in enhancing supply chain integration, operational efficiency, transparency, and the resilience of global logistics systems. This research adopts a qualitative-descriptive approach supported by a review of academic literature and the latest global industry practices. The findings indicate that digital transformation can enhance supply chain visibility, accelerate data-driven decision-making processes, reduce operational costs, and strengthen coordination among stakeholders across countries. However, the study also identifies several challenges, including data security risks, technological readiness gaps, high implementation costs, and organizational resistance to change. This research contributes conceptually by linking digital transformation initiatives to global supply chain performance. It is concluded that the success of digital transformation is not only determined by the adoption of technology but also by the alignment of organizational strategy, regulatory support, and sustainable human resource development.